2023
DOI: 10.3390/genes14061265
|View full text |Cite
|
Sign up to set email alerts
|

A Genome-Wide Analysis of a Sudden Cardiac Death Cohort: Identifying Novel Target Variants in the Era of Molecular Autopsy

Abstract: Sudden cardiac death (SCD) is an unexpected natural death due to cardiac causes, usually happening within one hour of symptom manifestation or in individuals in good health up to 24 h before the event. Genomic screening has been increasingly applied as a useful approach to detecting the genetic variants that potentially contribute to SCD and helping the evaluation of SCD cases in the post-mortem setting. Our aim was to identify the genetic markers associated with SCD, which might enable its target screening an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 86 publications
(95 reference statements)
0
4
0
Order By: Relevance
“…A particular interest was raised by the missense variant rs2228314 in the SREBF2 gene, associated with the metabolism of cholesterol, responsible for the insurgence of coronary atherosclerosis, a known cause of SCD. This hypothesis was also confirmed by the presence of CACNA1C, KCND2 and PRKAG2 variants all associated with lipid, cholesterol, arachidonic acid, and xenobiotics/drugs metabolisms [149]. Interestingly, the same study identified genetic variants mapping involved drug metabolism (i.e., ABCB1, ABCB2, CYP2E1, CYP2C9 and CYP2J2).…”
Section: Genomics and Epigenomics For Cod And Modmentioning
confidence: 63%
See 2 more Smart Citations
“…A particular interest was raised by the missense variant rs2228314 in the SREBF2 gene, associated with the metabolism of cholesterol, responsible for the insurgence of coronary atherosclerosis, a known cause of SCD. This hypothesis was also confirmed by the presence of CACNA1C, KCND2 and PRKAG2 variants all associated with lipid, cholesterol, arachidonic acid, and xenobiotics/drugs metabolisms [149]. Interestingly, the same study identified genetic variants mapping involved drug metabolism (i.e., ABCB1, ABCB2, CYP2E1, CYP2C9 and CYP2J2).…”
Section: Genomics and Epigenomics For Cod And Modmentioning
confidence: 63%
“…The findings of this study confirmed the presence of several genetic variants that can be associated with SCD. These results contribute to our understanding of the genetic factors underlying SCD and provide valuable insights for forensic pathology and clinical practice [149]. The study, employing Illumina sequencing, identified 25 SNPs that may be indicative of a potential pathogenic association with SCD.…”
Section: Genomics and Epigenomics For Cod And Modmentioning
confidence: 86%
See 1 more Smart Citation
“…Table S2: PRISMA 2020 Main Checklist. References [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 57 ] are cited in Supplementary Materials.…”
mentioning
confidence: 99%